Análise da vulnerabilidade ao HIV/AIDS de homens que fazem sexo com homens segundo práticas sexuais - Lima, Diego Jorge Maia (2014)
In the epidemiological context of AIDS, men who have sex with men has been a priority category for prevention, due to the adoption of unprotected sexual practices, the acquisition of risk behaviors and stigma and discrimination. Thus, a policy of effective prevention for this subgroup should be focused on the perspective of minimizing the vulnerability of groups, through action on the various individual, social and programmatic aspects. The study aims to analyze the vulnerability to HIV / AIDS in men who have sex with men from sexual practices. Cross-sectional and correlational study, conducted at two sites of gay sociability, located in the central region of the city of Fortaleza, Ceará . The study population consisted of men who have sex with men attending gay scene Fortaleza. The study sample was obtained by convenience and included 257 individuals. The instrument used was subjected to face validity and content by 03 judges and consisted of a structured form into four distinct parts: identification , sexual identity and history of sexual practices and sexual practices . Data collection took place during the months of December 2010 to March 2011. Associations between the dependent and independent variables of the study were investigated. We conducted bivariate analysis using the chi- square test with a significance level less than 0.05, to investigate the association between variables. The comparative analysis of means was performed by ANOVA and the Student t test. The results showed that as sociodemographics , age range 18-24 years, had 45.5 % (117), average 27.19 years, 89.2% (229) were literate, with at least completed high school singles, 86.4% (222), Catholic 52.9%(136) and 57.6% (148) browns. The facts of sexual identity, homosexual predominant preference for the term, with 44.7% (115) and family support was reported by 43.6% (112). The majority of respondents reported performing oral sex, accounting for 95.7 % (246). While 44 % (113) answered "do not use " condoms in oral sex . As for anal sex, almost all of the subjects reported practicing anal sex, which represented 98.4 % (253). It was revealed that 73.5% (189) of the subjects assumed the active and passive role in the relationship and that 71.6 %(184) of respondents reported using condoms " always ". Engaging in unprotected sexual intercourse statistically significant difference when associated with having a regular partner (p = 0.000), use of condoms in oral sex (p = 0.000) and anal sex (0.004). Notably, there is a remarkable influence of individual and social vulnerability in the determination of situations susceptibilities of the study group on HIV / AIDS, as the high rate of performing unprotected oral sex and significant association of unprotected sexual act with a regular partner. We recommend a specific approach to these factors for a better understanding of the AIDS epidemic in this segment. It is concluded that the susceptibility of the subgroup of men who have sex with men and the understanding of their specificities, still constitute a major challenge to be faced in all areas where hazardous conditions for the acquisition of HIV / AIDS are present.